Proposition D’une Demarche De Gestion Pour Reduire Les Risques De Conduite Des Projets D’implementation Des ERP Logistique - Kadouri, Abdillah; Ammi, Anouar (European Scientific Journal, ESJ, 2016)
The logistics activity exercise is in fact submitted to several constraints related to physical, financial and information flows; it also requires operational expenses optimization, compliance with performance indicators and processes control. Being structured in different integrated modules, the ERPs provide operational, tactical and strategic planning features that allow the company to balance its supply and demand plans. Although project management practices are considered effective nowadays, many companies are still struggling to implement these ERPs and automate the various logistics processes: indeed the situation of such projects becomes uncontrollable or they are abandoned. It is therefore appropriate to consider, in this article, the main risks that may arise during the logistics integration in the ERPs; then try to explain the most adequate governance to implement in order to reduce their impact.